2013
DOI: 10.1001/jama.2012.173925
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Medicare Advantage Plan Star Ratings and Enrollment

Abstract: Medicare's 5-star rating program for Medicare Advantage is associated with beneficiaries' enrollment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 19 publications
2
85
0
Order By: Relevance
“…Studies in the commercial market demonstrate associations between preferences and plans' costs, benefits, and quality, 7,16 and prior work demonstrates associations between Medicare Advantage star ratings and enrollment. 17 However, the relative importance of cost and quality in Medicare Advantage choices is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the commercial market demonstrate associations between preferences and plans' costs, benefits, and quality, 7,16 and prior work demonstrates associations between Medicare Advantage star ratings and enrollment. 17 However, the relative importance of cost and quality in Medicare Advantage choices is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Five star plans are additionally rewarded with the opportunity to enroll plan members all yearlong versus a 6 week time period beginning in October. Recent research suggests that higher star ratings are also associated with an increased likelihood that first-time enrollees will select that plan [41].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study evaluating the association between star ratings and enrollment decisions quantified the average value of increased ratings. Reid et al (2013) found that an increase in 1 star was associated with a 9.5% increased likelihood to enroll new enrollees. 21 Among members switching plans, for every 1-star increase there was a 4.4% increased likelihood to enroll.…”
Section: Figurementioning
confidence: 97%
“…Reid et al (2013) found that an increase in 1 star was associated with a 9.5% increased likelihood to enroll new enrollees. 21 Among members switching plans, for every 1-star increase there was a 4.4% increased likelihood to enroll. For MA-PD plans with consecutive low star ratings, increases in performance ratings will prevent a "Low Performing Icon" (LPI).…”
Section: Figurementioning
confidence: 97%